Early Detection and Intervention in Audiology An African perspective - Beswick, Rachael (Wits University Press, 2021)
"Early hearing detection and intervention (EHDI) is the gold standard for any practising audiologist, and for families of infants and children with hearing impairment. Yet EHDI remains a significant challenge for Africa, and various initiatives are in place to address this gap in transferring policy into practice within the southern African context. Early Detection and Intervention in Audiology: An African Perspective aims to address the diversity of factors in southern Africa that presents unique challenges to teaching and research in this field. The South African government's heightened focus on increasing access to health care, which includes ongoing Early Childhood Development (ECD) programmes, makes this an opportune time for establishing and documenting evidence-based research for current undergraduate and postgraduate students. Detailed case studies pay careful attention to contextual relevance and responsiveness to both identification and intervention in hearing impairment. With diverse contributions from local and international experts, but always with an African perspective, this textbook will be an essential resource for students, researchers and practitioners. "